SPECTRAL ANALYSIS OF HEART RATE VARIABILITY OF ATRIAL FIBRILLATION PATIENTS - Dolgova, I. V.; Yabluchansky, N.I.; Martimyanova, L.A.; Vahreneva, I.H. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The dependence of spectral characteristics of HRV from the complex of clinical features of AF of 64 patients at the age of 61±9 years was studied. The age and gender of the patients were analysed according to clinical features; the duration, course and form AF, severity of arterial hypertension (AH), functional class (FC) of angina pectoris, postmyocardium cardiosclerosis and valvular heart disease at which background AF took place, as well as FC of heart failure and types of reaction HR to orthostasis . HRV was researched on  5 minutes intervals of ECG in supine position. The HR, TP, VLF, LF and HF were estimated. The statistical processing of results was performed  with the help of Excel for Windows.The researches showed that AF is characterized by high power of a HRV spectrum with prevalence of high-frequency domain. The HRV changes do not depend on gender of the patients, duration and course of AF, but they were connected with age, AF form, orthostasis  reactions, FC of  heart failure and the severity of diseases which were the cause of AF. HRV parameters of  the aged patients were higher, under normocardial  AF, positive orthostatis reactions, lower FC of heart failure, but more severe degrees of hypertension and FC of angina pectoris.